Keefektifan Model Experiential Learning untuk Meningkatkan Kepedulian Siswa SMK Jurusan Keperawatan - Weni Kurnia Rahmawati (JKI (Jurnal Konseling Indonesia), 2015)
The lack of caring shown by the nurses can be seen from the number of public criticism towards the services they provided. The research problem in this study is whether the students’ caring of vocational nursing students can be improved through experiential learning model?. To answer the research question, equivalent time series design which comprised one pretest and four posttests of 6 respondents was conducted. The caring measurement of the subjects on the pretest, posttest 1, posttest 2, posttest 3, and posttest 4, used Concern Scale form A, A, B, C and D sequentially. Chronbach Alpha Test toward those four forms gave such results of reliability number: 0,838 for form A, 0.814 for form B, 0.750 for form C, and 0.723 for form D. It is said that the criterion validity for all test items is ≥ 0.361. Wilcoxon Sign Rank Test was applied to analyze the data. Results of this study indicates that the hypothesis test of posttest 1 to post-test 2 shows the significance number of 0,116 (≥ 0.05) so that Ho is accepted, the conclusion “there was no difference between the value of the posttest 1 and post-test 2 during the intervention at each subject of the research, or there were subjects of the research who got scores of post-test 2 smaller than the scores of the post-test 1.” It was found that the result of pretest to posttes1 is 0.027 (≤ 0.05), posttest 2 to posttest 3 is 0.027 (≤ 0.05) and posttest 3 to post-test 4 is 0.028 (≤ 0, 05) which concludes that there were differences of value during the process of intervention in each subject of the study. In conclusion, experiential learning model is effective to improve the students’ caring of vocational nursing students.